Report writing - Reid, Michelle (Palgrave Macmillan, 2015)
Aims to give students the understanding, confidence and tools to use report writing conventions to communicate their purpose, whatever their subject and whatever report they are writing. Real-life examples of student reports illustrate good writing style and effective communication. Diagrams and illustrations are used to make key points.